Sex-differences in Gluten-free Dietary Adherence and Clinical Symptoms in Patients with Long-term Treated Dermatitis Herpetiformis - Camilla Pasternack; Kaisa Hervonen; Eriika Mansikka; Timo Reunala; Katri Kaukinen; Teea Salmi (Medical Journals Sweden, 2022)
Dermatitis herpetiformis is a blistering autoimmune skin disease, and a cutaneous manifestation of coeliac disease. The burden of coeliac disease is increased especially in females, but studies concerning sex differences in patients with long-term treated dermatitis herpetiformis are scarce. This questionnaire study compared adherence to a gluten-free diet, clinical symptoms and well-being between females and males in a cohort of 237 long-term treated (median 24 years) patients with dermatitis herpetiformis. Females had better adherence to a gluten-free diet (p = 0.022) and they used dapsone significantly less often at the time of the study than did males (4% vs 13%, p = 0.017). The occurrence of skin symptoms was equal in both sexes, but dermatological quality of life was lower in females (p = 0.024), and gastrointestinal symptoms were more severe among females with dermatitis herpetiformis than among males (p = 0.027). In conclusion, long-term treated female patients with dermatitis herpetiformis have better adherence to a gluten-free diet, but they also experience more severe clinical symptoms compared with males.